THERMOCHRONOLOGY OF GRANITOID BATHOLITHS AND THEIR TRANSFORMATION INTO METAMORPHIC CORE COMPLEXES (EXAMPLE OF SONG‐CHAI MASSIF, NORTHERN VIETNAM) - A. G. Vladimirov; A. V. Travin; Phan Luu Anh; N. G. Murzintsev; I. Yu. Annikova; E. I. Mikheev; Nguyen Anh Duong; Tran Thi Man; Tran Thi Lan (Геодинамика и тектонофизика)
Based on the reconstruction of the thermal evolution of granitoid batholith, represented by the Song‐Chai gneiss‐granite massif (Northern Vietnam), the long‐term existence of granitoid magma at deep levels of the Earth's crust (H≥25 km, Δt~20–50 Ma) is established. The geodynamic analysis of the granitoid batholith and mathematical modeling of its thermal history shows that the magmatic chamber should be considered as a thermal trap at the lower level of the crust, which preserved residual granite melts for a long time. Activation of the magmatic chamber occurs in post‐collisional strike‐slip fault zones and is accompanied by tectonic exhumation of large crustal segments. As a result, the batholith is transformed into a Cordilleran‐type metamorphic core complex, residual rare‐metal melts are emplaced, and, commercial deposits are thus formed.